Manipulation of an α-glucosidase in the industrial glucoamylase-producing Aspergillus niger strain O1 to decrease non-fermentable sugars production and increase glucoamylase activity - Guo, Wenzhu; Liu, Dandan; Li, Jingen; Sun, Wenliang; Sun, Tao; Wang, Xingji; Wang, Kefen; Liu, Qian; Tian, Chaoguang (Frontiers in Microbiology, 2022)
Dextrose equivalent of glucose from starch hydrolysis is a critical index for starch-hydrolysis industry. Improving glucose yield and decreasing the non-fermentable sugars which caused by transglycosylation activity of the enzymes during the starch saccharification is an important direction. In this study, we identified two key α-glucosidases responsible for producing non-fermentable sugars in an industrial glucoamylase-producing strain Aspergillus niger O1. The results showed the transglycosylation product panose was decreased by more than 88.0% in agdA/agdB double knock-out strains than strain O1. Additionally, the B-P1 domain of agdB was found accountable as starch hydrolysis activity only, and B-P1 overexpression in ΔAΔB-21 significantly increased glucoamylase activity whereas keeping the glucoamylase cocktail low transglycosylation activity. The total amounts of the transglycosylation products isomaltose and panose were significantly decreased in final strain B-P1-3 by 40.7% and 44.5%, respectively. The application of engineered strains will decrease the cost and add the value of product for starch biorefinery.